CD36 expression on oral squamous cell carcinoma cells correlates with enhanced proliferation and migratory activity. (3rd March 2020) - Sakurai, Kotaro; Tomihara, Kei; Yamazaki, Manabu; Heshiki, Wataru; Moniruzzaman, Rohan; Sekido, Katsuhisa; Tachinami, Hidetake; Ikeda, Atsushi; Imaue, Shuichi; Fujiwara, Kumiko; Noguchi, Makoto
Abstract: Objective: Recent studies have demonstrated the pro‐tumour role of CD36 in multiple cancer types. However, its role has not been well elucidated in oral squamous cell carcinoma (OSCC). Here, we aimed to evaluate the role of CD36 in proliferation and migration of OSCC cells. Methods: Human OSCC cell lines HSC‐2, HSC‐3, HSC‐4 and Ca9‐22 were assessed for proliferation by staining with the cell proliferation marker Ki‐67. We also assessed migration activity, and the expression of cell adhesion molecules such as E‐cadherin and β‐catenin and platelet‐derived growth factor receptors (PDGFRs) of CD36‐positive cells. Results: CD36‐positive cells showed increased expression of Ki‐67 and migration activity compared with CD36‐negative cells. Moreover, CD36‐positive cells showed reduced expression of E‐cadherin and β‐catenin, whereas the expression of PDGFRs increased compared with that in CD36‐negative cells. Conclusions: Our results strongly suggest that CD36 has an important role in facilitating the proliferation and migration activity of OSCC cells, indicating its usefulness in the diagnosis of high‐grade tumour and targeted therapy of oral cancer.